(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Study of the speech of stuttering children in the article. Methods for the development of independent speech in stuttering children, speech therapy, educational work and cooperation with parents. About moving breathing exercises in stuttering children and point massages that treat stuttering children.